Preventing prematurity: The power of determining factors and challenges in a rural district hospital in Benin - SAIZONOU, JACQUES Z.; MONGBO, Virginie; AFFO, PATRICK JEAN-CLAUDE (My University, 2021)
Preterm births remain a major public health issue due to its weight in neonatal mortality and the significant socio-economic costs for its care. The aim of the current study was to identify factors associated with preterm births at Allada-Toffo-Zè zone hospital in Benin. This was a case-controlling study, which took place in April 2019. A total of 222 women's files were examined, including 74 cases and 148 controlling samples. Socio-demographic data, health status during pregnancy, previous state of being and health system were collected. Conditional logistic regression was used to identify explanatory factors for prematurity via Stata 15. The prematurity rate was 9.4%. Self-medication OR = 4.99 with 95% CI = [1.71-14.5], alcohol consumption OR = 19.55 with 95% CI = [5.89-64.90], threat to premature birth OR = 3.88 with 95% CI = [1.04-14.35], the mother's occupation OR = 13.22 with a 95% CI = [1.65-105.66] were related to prematurity. Prematurity is a problem that requires corrective actions. Promoting empowerment of women which guarantees good health during pregnancy, as well as enhancing health staff skills will significantly reduce preterm births at Allada-Toffo-Zè district hospital.
Keywords: Prematurity; factors; determinants; district; Allada-Toffo-Zè; Benin.